Question
Answers

Solve the following trigonometric equation:
$3{\cos ^2}\theta - 2\sqrt 3 \cos \theta \sin \theta - 3{\sin ^2}\theta = 0$.

Answer Verified Verified
Hint: By the use of trigonometric formulae we need to find the value of $'\theta '$ satisfying the given equation.
Given,
$3{\cos ^2}\theta - 2\sqrt 3 \cos \theta \sin \theta - 3{\sin ^2}\theta = 0 \to (1)$
Now, we can rewrite the equation (1) as
$
   \Rightarrow 3({\cos ^2}\theta - {\sin ^2}\theta ) - \sqrt 3 (2\cos \theta \sin \theta ) = 0 \\
   \Rightarrow 3({\cos ^2}\theta - {\sin ^2}\theta ) = \sqrt 3 (2\cos \theta \sin \theta ) \to (2) \\
$
We know that $\cos 2\theta = {\cos ^2}\theta - {\sin ^2}\theta $ and $\sin 2\theta = 2\sin \theta \cos \theta $. Substituting in equation (2), we get
$
   \Rightarrow 3\cos 2\theta = \sqrt 3 \sin 2\theta \\
   \Rightarrow \dfrac{3}{{\sqrt 3 }} = \dfrac{{\sin 2\theta }}{{\cos 2\theta }} \\
   \Rightarrow \tan 2\theta = \sqrt 3 \\
$
Now, let us write the value of $\sqrt 3 $ in terms of $\tan $ i.e.., $\tan (\dfrac{\pi }{3}) = \sqrt 3 $, Substituting in the above equation, we get
$
   \Rightarrow \tan 2\theta = \tan (\dfrac{\pi }{3}) \\
   \Rightarrow 2\theta = n\pi + \dfrac{\pi }{3} \\
   \Rightarrow \theta = \dfrac{{n\pi }}{2} + \dfrac{\pi }{6} \\
 $
Hence, the value of $'\theta '$ satisfying the given equation is $\dfrac{{n\pi }}{2} + \dfrac{\pi }{6}$, where n is an integer.
Note: Here, we have added $'n\pi '$ to the $\dfrac{\pi }{3}$ after cancelling the tan on the both sides as $'\pi '$ is the period of the tan function and n is an integral number.

Bookmark added to your notes.
View Notes
×